Investigation of using Calabrian pine cone dust and borax in brake pads - Sugozu, Ilker; Can, Ibrahim; Oner, Cengiz (Emerald Group Publishing Limited, 2014)
Purpose - The purpose of this paper is to investigate use of calabrian pine (pinus brutia) cone (CPC) dust along with borax (BX) to assess the effect of friction coefficient. Despite the number of research studies completed on the mechanism of friction in automotive brake lining materials, the phenomenon is still not fully understood. Complex mechano-chemical processes occurring on the friction interface of a composite friction material make it difficult to understand the correlation between the formulation of brake lining and the frictional performance. Design/methodology/approach - In this study, the use of CPC dust along with BX has been investigated for assessing the effect on friction coefficient. CPC has resin in it. BX is a boron production which is widely used in boron glass production and in ceramic industry for increasing the heat-resistant and - forming abrasion resistant. Newly formulated brake lining material with five different ingredients has been tested under Friction Assessment and Screening Test. Friction coefficient, wear rate and scanning electron microscope for friction surface were examined to assess the performance of these samples. Findings - Analysis of the experimental results shows that the brake lining material containing CPC and BX significantly improved the stability of the friction coefficient, fade and wear resistance. Originality/value - Several investigations have been conducted to use different materials in brake pads. The brake pad standards have been provided in previous studies, as well as the aims for economical and sustainable production. In the present study, production of brake pads by CPC dust and BX has been executed. Parallel results have been presented between previously reported and present study, in view of brake characteristics and wear resistance. Use of the lower cost and productive organic sources of material are the main improvement of the present study.
Keywords: Friction; Wear resistance; Composite materials